Językowa konceptualizacja czasu w tynieckim przekładzie Biblii - Szagun, Dorota (Acta Universitatis Lodziensis. Folia Linguistica, 2014)
This article attempts to characterise various verbal connections with the word time in Tyniec translation of the Bible. Expressions with the word time give ample material, allowing for multi-linguistic analysis, it is more than 800 examples of the word time (684 in the Old Testament and 160 in the New Testament), after taking account of other word units associated with the determination of time, it is more than 4,000 word units. Expressions with the word time in Polish edition of the Bible reflect the mind-set and culture, manifested in the Polish language, of course, inextricably linked with the biblical Semitic motivations. Time in the Bible is thus conceptualized as a measurable physical quantity, synthesizing different units of measure: size, length, but also the weight (e.g. hard times), a certain continuity of religious events focused on eternity and as a sacred cycle. The clearest expression seems to be the right time, understood as a convenient, appropriate moment.